Late Jurassic–Early Cretaceous continental convergence and intracontinental orogenesis in East Asia: A synthesis of the Yanshan Revolution. (15th December 2015) - Dong, Shuwen; Zhang, Yueqiao; Zhang, Fuqin; Cui, Jianjun; Chen, Xuanhua; Zhang, Shuanhong; Miao, Laicheng; Li, Jianhua; Shi, Wei; Li, Zhenhong; Huang, Shiqi; Li, Hailong
Abstract: The basic tectonic framework of continental East Asia was produced by a series of nearly contemporaneous orogenic events in the late Middle Jurassic to Early Cretaceous. Commonly, the Late Mesozoic orogenic processes were characterized by continent–continent collision, large-scale thrusting, strike-slip faulting and intense crustal shortening, crustal thickening, regional anatexis and metamorphism, followed by large-scale lithospheric extension, rifting and magmatism. To better understand the geological processes, this paper reviews and synthesizes existing multi-disciplinary geologic data related to sedimentation, tectonics, magmatism, metamorphism and geochemistry, and proposes a two-stage tectono-thermal evolutionary history of East Asia during the late Middle Jurassic to Early Cretaceous (ca. 170–120 Ma). In the first stage, three orogenic belts along the continental margins were formed coevally at ca. 170–135 Ma, i.e., the north Mongol–Okhotsk orogen, the east paleo-Pacific coastal orogen, and the west Bangong–Nujiang orogen. Tectonism related to the coastal orogen caused extensive intracontinental folding and thrusting that resulted in a depositional hiatus in the Late Jurassic, as well as crustal anatexis that generated syn-kinematic granites, adakites and migmatites. The lithosphere of the East Asian continent was thickened, reaching a maximum during the latest Jurassic or the earliest Cretaceous. In the second stage (ca. 135–120 Ma), delamination of the thickened lithosphere resulted in a remarkable (>120 km) lithospheric thinning and the development of mantle-derived magmatism, mineralization, metamorphic core complexes and rift basins. The Middle Jurassic–Early Cretaceous subduction of oceanic plates (paleo-Pacific, meso-Tethys, and Mongol–Okhotsk) and continent–continent collision (e.g. Lhasa and Qiangtang) along the East Asian continental margins produced broad coastal and intracontinental orogens. These significant tectonic activities, marked by widespread intracontinental orogeny and continental reconstruction, are commonly termed the Yanshan Revolution (Movement) in the Chinese literature.